PENERAPAN METODE EVERYONE IS TEACHER HERE UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V DI SDIT WANASABA - Sabahiyah; Khairul Huda (Journal of Mandalika Literature, 2021)
The purpose of this study is to increasing the students' motivation to learn by using the method everyone is teacher here for class V SDIT Wanasaba. The methode of the research is a classroom action research (Classroom management) which was carried out for two cycles, each cycle consisting of four stages of activity, namely, planning stage, taking action stage, observing stage and reflecting stage. The subjects in this study were fifth grade of students SDIT Wanasaba, totaling 26 people consisting of 11 boys and 15 girls. Students' learning motivation data was collected using a questionnaire, after the data was collected it was then analyzed descriptively. The data of student learning motivation has increased, in the first cycle the average student motivation is 20.42 and is in the sufficient category and the second cycle the average student learning motivation is 26.92 in the good category. Based on these data, it can be concluded that the everyone is teacher here method can increase students' learning motivation.